2020
DOI: 10.3390/agronomy10081097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moderately-Reduced Water Supply and Picking Time on the Chemical Composition of Pickling Cucumber (Cucumis sativus L.) in Open Field Cultivation

Abstract: As climate change evokes changing precipitation patterns, the cultivation of vegetable crops in open fields might become more difficult in the future. Nowadays, many vegetable growers are already facing relatively long unprecedented precipitation-free periods. In many growing regions, irrigation is only available to a limited extent or not at all, and the cultivated plants will suffer from moderate water stress more often. Therefore, we examined the effects of moderately-reduced water supply on the chemical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Literature data demonstrate the sodium content of cucumber fruits across different fertilisation versions, ranging from 1.08 ppm to 1.50 ppm [67]. Additionally, the zinc content of cucumber fruit exhibits wide variation, ranging from 0.20 ppm in mesocarp analyses to 0.43 ppm in exocarp analyses [68]. These findings provide valuable insights into the macroelement and microelement compositions of various generative organ consumption species.…”
Section: Results On Yield Qualitymentioning
confidence: 83%
“…Literature data demonstrate the sodium content of cucumber fruits across different fertilisation versions, ranging from 1.08 ppm to 1.50 ppm [67]. Additionally, the zinc content of cucumber fruit exhibits wide variation, ranging from 0.20 ppm in mesocarp analyses to 0.43 ppm in exocarp analyses [68]. These findings provide valuable insights into the macroelement and microelement compositions of various generative organ consumption species.…”
Section: Results On Yield Qualitymentioning
confidence: 83%
“…The minor rainy season presented higher mean length, number and weight of fruits than the major rainy season. This could be due to improved assimilate deposition in the sink tissues of fruits as a result of improved dissolution and transport of water, mineral and organic materials from increased precipitation during the minor rainy season [45] Schlering et al [46] found that the quality of cucumber crop could suffer if the right abiotic factors of water and soil nutrients are deficient.…”
Section: Figure 9 Effect Of Gypsum and Seasonal Variability On Number Of Leavesmentioning
confidence: 99%
“…Cucumber cultivation management varies depending on crop type, temperature, lighting quality, and management methods (Lee, 2012;Ashraf et al, 2020;Cui et al, 2020;Kowalczyk et al, 2020;Schlering et al, 2020;Wang et al, 2020). For example, early-morning heating is applied to raise temperatures (Kwon et al, 2004), and studies are being conducted on the effects of light conditions and inhibition of ventilation using shading and fog during high temperatures (Ashraf et al, 2020;Kim et al, 2020;Kowalczyk et al, 2020;Park et al, 2020).…”
Section: Introductionmentioning
confidence: 99%